Term of Child in Analysis of Languages Various By The Quran - Ruslan Wahab; Mardyawati Y (Lembaga Sembilan Tiga Community, 2021)
The Quran in its multi-function, not only studies in the world of religion but also flows to academic interests to become a source of scientific studies from various disciplines, including linguistic sciences. Even Arabic scholars agree to place the Quran as the first and foremost source in determining the Nahwu rules (syntax) of Arabic through the qiyas approach. One of the concepts that is the object of study that comes from the Koran is the term child. The linguistic facts show that the Quran uses several words to express the meaning of the word child; namely: al-walad, al-Thifl, al-ibn, al-bint, al-dzurriyat, hafadah, al-shabiy, al-ghulam. This article reveals the use of various languages used by the Quran in the word children. With the hope of being able to reveal how much the Quran is very systematic in arranging a language that harmonizes between linguistic rules and social rules that exist in the language-speaking community.